Serological Basis for Use of Meningococcal Serogroup C Conjugate Vaccines in the United Kingdom: Reevaluation of Correlates of Protection - Borrow, Ray (American Society for Microbiology, 2001)
The antibody data supporting the use of meningococcal serogroup C conjugate (MCC) vaccines in the United Kingdom were generated by serum bactericidal assay (SBA) using rabbit complement (rSBA). This may give higher titers than those obtained with human complement (hSBA), for which the “gold standard” correlate of protection for meningococcal C disease is a titer of ≥4. Comparison of rSBA and hSBA titers in sera from unvaccinated adults with an rSBA titer of ≥8 showed that for 93% (27 of 29) the titer was ≥4 by hSBA, confirming natural protection. Furthermore, sera from MCC vaccinees showed that an rSBA titer of <8 or ≥128 discriminated susceptibility and protection well (85% with rSBA titers of <8 had hSBA titers of <4, and 99% with rSBA titers of ≥128 had hSBA titers of ≥4). However, discrimination was poor in the rSBA titer range 8 to 64, with only 60% having hSBA titers of ≥4. In such cases we propose that protection can be assumed if there is a fourfold rise in titer between pre- and postvaccination sera or if there is a characteristic booster response to a polysaccharide challenge dose with, if available, evidence of antibody avidity maturation or an hSBA titer of result ≥4. Applying these criteria to toddlers, 10 to 40% of whom had titers in the range 8 to 64 after a single dose of MCC vaccine, showed that 94% had a fourfold rise in titer, including 98% of those in the titer range 8 to 64. In addition, of those with titers of <128 post-MCC vaccination, 90% had titers of ≥128 after a 10-μg polysaccharide booster dose, compared with only 7% of unprimed age-matched toddlers given a full 50-μg dose. Furthermore, the increase in geometric mean avidity index pre- and postbooster was independent of post-primary MCC titer. These results indicated that the majority of toddlers with an rSBA titer between 8 and 64, and some of those with an hSBA result of <4, have mounted a protective immune response with the induction of immunological memory.